Overcoming the «two cultures». Culture, science and philosophy: convergences and new challenges - Wagner, Astrid (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Today we still live with the stereotype of the two cultures, with the idea of a certain incommunicability between so-called hard sciences and humanities, and in general, between the sphere of science and that of culture. This article presents a philosophical vision of the relationship between culture and science beyond the topical dichotomy, sustaining instead an approach in which science is conceived as a cultural phenomenon. A historical-systematic overview of some milestones of the philosophy of culture and the philosophy of science shows how both interpenetrate and influence each other. Focusing on the confluences between both allows to address a series of concerns and challenges that affect the field of epistemology as a whole: facing cognitive vulnerability and the complexity of the epistemic conditions of human beings; confronting the most extreme positions of both relativism and fundamentalism; developing a concept of epistemic responsibility in the different fields of knowledge to counteract the culture of mistrust and the perception of our time as the posttruth era.